2012
DOI: 10.1111/j.1365-2230.2011.04256.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet A1 phototherapy: a British Photodermatology Group workshop report

Abstract: SummaryWhole-body ultraviolet (UV)A1 (340-400 nm) phototherapy was first introduced 30 years ago, but is currently available in the UK in only three dermatology departments. A workshop to discuss UVA1 was held by the British Photodermatology Group in May 2009, the aim of which was to provide an overview of UVA1 phototherapy and its role in practice, and to identify areas in which further studies are required. The conclusions were that UVA1 phototherapy is an effective treatment in several inflammatory skin dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 29 publications
0
33
0
11
Order By: Relevance
“…UVA1 light has a deeper penetrance depth and provides much more tanning than PUVA and narrowband UVB, and thus initial uses were for phototesting or cosmetic purposes [5][6][7][8][9] . However, in the early 1990s, Krutmann and Schöpf [10] described for the first time that UVA1 phototherapy can be effectively used to treat atopic dermatitis.…”
mentioning
confidence: 99%
“…UVA1 light has a deeper penetrance depth and provides much more tanning than PUVA and narrowband UVB, and thus initial uses were for phototesting or cosmetic purposes [5][6][7][8][9] . However, in the early 1990s, Krutmann and Schöpf [10] described for the first time that UVA1 phototherapy can be effectively used to treat atopic dermatitis.…”
mentioning
confidence: 99%
“…Lupus eritematozusta düşük doz, diğerlerinin tümünde orta doz UVA1 önerilmektedir. Etkili olabileceği diğer hastalıklar arasında kutanöz T hücreli lenfoma, sklerödem, nefrojenik sistemik fibrozis, nekrobiyozis lipoidika, kronik ürtiker, granüloma anülare, kutanöz sarkoidoz ve Graft versus host hastalığı sayılabilir (51)(52)(53).…”
Section: Ultraviyole A1unclassified
“…Eritem, herpes simpleks reaktivasyonu, polimorf ışık erüpsiyonu diğer yan etkiler arasında sayılabilir. İlaçlarla indüklenen fotosensitivite başlıca UVA spektrumunda gerçekleştiği için, UVA1 tedavisi sırasında fotoaktif ilaç kullanımı fototoksisiteye yol açabilir (51)(52)(53).…”
Section: Yan Etkilerunclassified
See 1 more Smart Citation
“…The deeper penetration and lower phototoxicity of long-wavelength Ultraviolet light A (UVA, 320-400 nm) compared to that of shortwavelength UV light (200-320 nm) provided a rational for scientists to investigate the di®erent e®ects of UVA on human health. 1,2 UVA has been demonstrated to be e®ective in the treatment of sclerotic skin diseases 3 and, at appropriate doses, resulted in the up-regulation of the heme oxygenase-1, which played an important role in protection of skin. 4,5 EI-Mofty et al suggested that the e±cacy of UVA phototherapy in the treatment of localized scleroderma was mainly obtained by the increased production of collagenase.…”
Section: Introductionmentioning
confidence: 99%